A supersensitive wearable sensor constructed with PDMS porous foam and multi-integrated conductive pathways structure. Issue 3 (1st February 2023) - Xu, Bingbing; Ye, Feng; Chen, Ronghu; Luo, Xiaogang; Xue, Zhebin; Li, Ruoxin; Chang, Guangtao
Abstract: In recent years, wearable multifunctional strain sensors have attracted attention for their promising applications in wearable electronics and portable devices. To achieve a high-performance wearable strain sensor with a wide sensing range and high gauge factor (GF), wisely choosing appropriate conductive materials and a rational structural design is essential. Herein, we develop a supersensitive sensor that contains one-dimensional conductive material CNT and two-dimensional material MXene built on a PDMS porous foam that is made based on a sugar template. The one-dimensional carbon nanotube (CNT) functionalizes as a conductive scale layer through solvent swelling and evaporation on the surface of the PDMS skeleton. The two-dimensional MXene is applied on top of the CNT layer to form final conductive pathways. The PDMS/CNT@MXene (PCM) sensor has a wide sensing range (150%), high sensitivity (GF = 26438), rapid response speed (response/recovery time of 60/71 ms), and exceptional durability (>1000 cycles) owing to its unique porous structure with scale layers and graded fracture of conductive pathways. Moreover, the PCM sensor is capable of monitoring subtle and significant human activities and is used for wireless sensing and medical diagnostics, even for solvent identification. The superior performance of the PCM sensor provides vast application potential in human movement, health monitoring, and warning devices.